Implementasi Financial Literacy Dalam Upaya Meningkatkan Financial Performance Pada Keberlangsungan Usaha Koperasi: Studi Kasus Pada Gabungan Koperasi Susu Indonesia (GKSI) Daerah Jawa Barat - Nurhayat Indra; M. Ardi Nupi H; Gumilar Pratama (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The purpose of this research is to know the level of implementation of cooperative’s financial literacy in an effort to increase financial performance in cooperative’s business sustainability at the GKSI West Java Regional. Based on the research result that the level of financial literacy of administrators and managers are in Sufficient Literate (Quite Intellect), afterwards there are also supported by the indirect cash flow data which is in the third (3) cash flow pattern, it means the operating cash flow and financing cash flow is in positive (+) pattern, however the investment cash flow is in negative (-) pattern. Based on the financial performance from liquidity ratio, the cooperative is in very unwell criteria because the cooperative’s interval ratio is >300%, and from the activity ratio, the cooperative is in very unwell criteria because the cooperative’s interval ratio is <6 times, and from the leverage ratio, the cooperative is in well criteria because the cooperative’s interval ratio is <40%, and from the profitability ratio, the cooperative is in very unwell criteria because the cooperative’s interval ratio is <3%. Based on trend analysis, the sales forecasting rate for the next 5 years will be decreased every year. Then, it can be concluded that the administrators and managers have to reincrease their financial literacy to increase financial performance in its cooperative’s business sustainability.